SIDEROPHILE-ELEMENT ANOMALIES IN CK CARBONACEOUS CHONDRITES: IMPLICATIONS FOR PARENT-BODY AQUEOUS ALTERATION AND TERRESTRIAL WEATHERING OF SULFIDES - Huber H.; Rubin A.E.; Kallemeyn G.W.; Wasson J.T. (My University, 2006)
CK chondrites constitute the most oxidized anhydrous carbonaceous chondrite group; most of the Fe occurs in magnetite and in FeO-rich mafic silicates. The two observed CK falls (Karoonda and Kobe), along with thirteen relatively unweathered CK finds, have unfractionated siderophile-element abundance patterns. In contrast, a sizable fraction of CK finds (9 of 24 investigated) shows fractionated siderophile abundance patterns including low abundances of Ni, Co, Se and Au; the most extreme depletions are in Ni (0.24 of normal CK) and Au (0.14 of normal CK). This depletion pattern has not been found in other chondrite groups. Out of the 74 CK chondrites listed in the Meteoritical Bulletin Database (2006; excluded considerably paired specimens; see http://tin.er.usgs.gov/meteor/metbull.php) we analyzed 24 and subclassified the CK chondrites in terms of their chemical composition and sulfide mineralogy: sL (siderophiles low; six samples) for large depletions in Ni, Co, Se and Au (>50% of sulfides lost); sM (siderophiles medium; two CKs) for moderately low Ni and Co abundances (sulfides are highly altered or partly lost); sH (siderophiles high; one specimen) for enrichments in Ni, Co, Se and Au; ’normal’ for unfractionated samples (13 samples). The sole sH sample may have obtained additional sulfide from impact redistribution in the parent asteroid. We infer that these elements became incorporated into sulfides after asteroidal aqueous processes oxidized nebular metal; thermal metamorphism probably also played a role in their mineral siting. The siderophile losses in the sL and sM samples are mainly the result of oxidation of pentlandite, pyrite and violarite by terrestrial alteration followed by leaching of the resulting phases. Some Antarctic CK chondrites have lost most of their sulfides but retained Ni, Co, Se and Au, presumably as insoluble weathering products. ? 2006 Elsevier Inc. All rights reserved.
Keywords: CARBONACEOUS CHONDRITE; CHEMICAL COMPOSITION; FRACTIONATION; IMPACT STRUCTURE; MINERALOGY; PARENT BODY; SIDEROPHILE ELEMENT; SULFIDE; WEATHERING